2021
DOI: 10.18087/cardio.2021.2.n1314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Total Ischemic Time on Clinical Outcomes in Patients with ST-Segment Elevation Myocardial Infarction

Abstract: Aim      To evaluate the effect of the total time of myocardial ischemia on results of the treatment of patients with ST segment elevation acute myocardial infarction (STEMI) who underwent percutaneous coronary interventions (PCI).Material and methods This study used data from a hospital register for PCI in STEMI from 2006 through 2017. 1649 patients were included. Group 1 consisted of 604 (36.6 %) patients with a total time of myocardial ischemia not exceeding 1880 min; group 2 included 531 (32.2 %) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The total time of myocardial ischemia was frequently reported to be associated with an increased incidence of the no-reflow phenomenon. 30,31 Research revealed that prolonged total ischemic time was an independent predictor of the no-reflow phenomenon. 32 The present study depicted that no matter how long the time of myocardial ischemia (2-6 h), ferroptosis only occurred during the reperfusion phase, and the myocardial injury was alleviated after the administration of a ferroptosis inhibitor -Fer-1.…”
Section: Discussionmentioning
confidence: 99%
“…The total time of myocardial ischemia was frequently reported to be associated with an increased incidence of the no-reflow phenomenon. 30,31 Research revealed that prolonged total ischemic time was an independent predictor of the no-reflow phenomenon. 32 The present study depicted that no matter how long the time of myocardial ischemia (2-6 h), ferroptosis only occurred during the reperfusion phase, and the myocardial injury was alleviated after the administration of a ferroptosis inhibitor -Fer-1.…”
Section: Discussionmentioning
confidence: 99%
“…Так в исследовании И. С. Бессонова и соавт. было показано, что увеличение времени до реваскуляризации >360 мин коррелирует с большей частотой возникновения феномена невосстановленного кровотока [26]. Чем дольше продолжается ишемия миокарда, тем больше повреждается клеток и тканей, происходит эскалация таких процессов, как набухание эндотелиоцитов, адгезия лейкоцитов к внутренней оболочке артерий, обтурация лейкоцитами и тромбоцитами капилляров, повышение сосудис той проницаемости и межклеточный отек, диапедез эритроцитов и нейтрофилов.…”
Section: феномен невосстановленного коронарного кровотока No Reflow P...unclassified
“…The longer the ischemia time in STEMI patients, the higher the incidence of no-reflow. [10] A STEMI registry study demonstrated that the 6-month mortality of patients undergoing primary PCI (PPCI) increased by 0.18% for each 10 min delay in door-balloon time. [11] In addition to optimizing the reception process of patients with STEMI, it is vital to strengthen public health education, popularize medical knowledge, and shorten patients visiting time.…”
Section: Ischemia and Reperfusion Injurymentioning
confidence: 99%